Development of a measure of therapy provision for spasticity management in the paretic lower limb – the Leg Therapy recording Schedule (LegTS). Issue 4 (13th February 2018) - Ashford, Stephen; Jackson, Diana; Turner-Stokes, Lynne
Abstract: Purpose: In rehabilitation studies, it is critical to understand the constituents of interventions. First, to enable replication of the work and second, to identify what treatments work best. The development of a tool to describe and quantify therapy interventions in the context of focal spasticity management is presented. Methods: Potential intervention categories were identified from: (a) retrospective analysis of prospectively collected data from a cohort of patients ( n  = 62) receiving physical interventions in the context of botulinum toxin (BoNT) injection for leg spasticity and (b) cognitive de-briefing with Patient and Carer Advisory Group (PCAG) of patient and carer dyads ( n  = 8). Item reduction was achieved through consultation with a purposively-selected group of physiotherapists and occupational therapists ( n  = 16) in a two-round Delphi process. This was followed by review of findings by PCAG members. Results: A list of 24 possible therapy categories were identified and then reduced, resulting in a tool with two domains: (1) postural management; four categories and (2) exercise and retraining; four categories. The Leg Therapy recording Schedule (LegTS) wording and presentation were refined for clinical and research use. Conclusions: The LegTS is designed to record therapy interventions for the paretic lower limb in the context of spasticity intervention. Content and face validity have initially been addressed within the development process. Implications for Rehabilitation: Clinicians need to understand intervention effectiveness, and to do so, it is critical to capture all the components of a complex intervention. In clinical practice or research, patient experience measures are required to capture the complexity of intervention provided and monitor intervention effectiveness on a case by case basis. Clinicians involved in rehabilitation and management of focal spasticity in the leg can use the Leg Therapy recording Schedule (LegTS) to enable an understanding of the entirety of the intervention package provided.